Analisis belanja daerah menurut urusan dan hubungannya terhadap jumlah pengangguran di Provinsi Jambi - Danal Al Ahlul Naza; Selamet Rahmadi; Rosmeli Rosmeli (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
This study aims to determine and analyze: 1). The dynamics of regional expenditure development according to functions, namely mandatory and optional functions as well as the number of unemployed people in Jambi Province during the period 2008 - 2018, 2). Allocation of regional expenditure to regional expenditure according to mandatory and optional functions in Jambi Province during the period 2008 - 2018 and 3). The relationship between regional expenditure according to mandatory functions and optional functions to the number of unemployed people in Jambi Province during the period 2008-2018. The data analysis method used in this study was the Pearson development, ratio, and correlation formulas. Based on the results of research during the years 2010-2018, the results are regional expenditure according to mandatory functions, regional expenditure according to selected functions, and the number of unemployed in Jambi Province has increased on average. The allocation of regional expenditures according to mandatory functions and regional expenditures according to selected functions in Jambi Province has increased on average. Expenditures according to mandatory functions and expenditures according to selected functions have a very strong and negative relationship to the number of unemployed in Jambi Province during 2010-2018 at α = 1% two-tailed (2-tailed) test. Keywords: Obligatory affairs, regional spending according to selected functions, the number of unemployed